The Role of Spiritual Care in Promoting Health and Well-Being Among Patients with Chronic Illnesses: A Systematic Review and Meta-Analysis - Manisha Manisha; Aris Citra Wisuda; Tukimin bin Sansuwito; Idris Adewale Ahmed (Public Health of Indonesia, 2026)
Background: Chronic illnesses are often accompanied by prolonged psychological stress and a decline in spiritual well-being, both of which can negatively affect patients’ health, coping ability, and overall quality of life. Spiritual care has emerged as a key component of holistic, patient-centered care, promoting emotional stability and spiritual resilience in those managing chronic conditions. Objective: This systematic review and meta-analysis aimed to evaluate the effectiveness of spiritual care interventions in reducing stress and enhancing spiritual well-being among adults with chronic illnesses. Methods: A systematic search was conducted using PubMed, Scopus, Google Scholar, and ScienceDirect to identify relevant RCTs published between 2020 and 2025. Studies were included if they involved adults (≥18 years) diagnosed with chronic diseases and implemented spiritual care as the primary intervention. Data screening, extraction, and synthesis followed PRISMA 2020 guidelines. Ten RCTs met the eligibility criteria and were included in the qualitative synthesis, with meta-analysis performed where applicable. Results: Spiritual care interventions such as prayer therapy, mindfulness-based spiritual practices, religious rituals, and structured spiritual counseling demonstrated statistically significant effects in reducing stress levels and improving spiritual well-being across varied patient populations, including those with cancer, diabetes, cardiovascular, and renal conditions. Interventions were typically delivered by trained nurses, chaplains, or multidisciplinary teams over 4 to 8 weeks. Conclusion: Spiritual care is effective in managing psychological and spiritual challenges in chronic illness, supporting its integration into holistic, person-centered healthcare.